Mathematical errors in advanced calculus: A survey among engineering students / Maisurah Shamsuddin … [et al.] - Shamsuddin, Maisurah; Mahlan, Siti Balqis; Umar, Norazah; Alias, Fadzilawani Astifar (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2015)
Mathematics is widely used in all areas of learning. Students who do not master the basic mathematics will face many problems in learning at the advanced level. This study was conducted to identify the mathematical errors and misconceptions in advanced calculus. The related topics are differentiation of two variables, method of integration, and differential equation. A sample of 80 students’ final examination answer sheets for the subject of MAT235 was closely examined to identify the mathematical errors and misconceptions. The technique used to collect the data is quantitative method using descriptive analysis. The findings of this study showed that most of the students were still weak in mastering mathematical basic facts and concepts. The weakness in understanding the basic concepts may lead them to use the wrong strategy when solving mathematics questions. This misconception should be identified by the lecturers and rectified by the students in order to enhance their learning in higher education.